The Small UWB Monopole Antenna with Stable Omnidirectional Radiation Pattern - Firdaus, -; Yuhanef, Afrizal; Yulindon, Yulindon; Meidelfi, Dwiny; Silvana, Meza (Society of Visual Informatics, 2022)
Ultra Wideband (UWB) technology is an unmodulated wireless digital communication system that uses an extremely short duration pulse to transmit information bit. Because of this pulse, the UWB system needs a very wide bandwidth. Federal Communication Commission (FCC) has regulated the 3.1 – 10.6 GHz frequency spectrum for UWB. Since FCC released this frequency, many research in telecommunication have been done on UWB systems. One of them is a development of an Antenna that is suitable for UWB devices. UWB antenna characteristics require FCC band, omnidirectional radiation pattern, and compact size. In order to meet these needs, an antenna with a simple structure in the form of a monopole patch antenna with a similar patch size and ground width has been designed. The antenna is built on an FR4 – epoxy substrate material, with 4.4 dielectric constant and 1.6 mm thickness. The antenna feeding structure consists of two 100 Ω and 50 Ω lines with a wideband impedance matching scheme using tapered side and tapered transformers. The antenna design and optimization processes are conducted using electromagnetic simulation software, and measurements are carried out in an anechoic chamber. Simulation and measurement results show good agreement, and the antenna can work at frequencies 3.5 - 11.3 GHz with a gain of 1.5 – 3.25 dBi and stable omnidirectional radiation patterns. The antenna has dimensions of 27 × 8 × 1.6 mm, which are smaller than the antenna reported in the last research and suitable to be applied on various UWB devices.